An Analytical Network Process (ANP) Approach to the Public Policy Innovation Strategy Model: A Case Study of Pamekasan Regency Tourism - Jordan Putra Cahyono (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2024)
This study explores the innovation model and the role of public policy in tourism development within Pamekasan Regency, utilizing the Analytical Network Process (ANP) approach. It primarily seeks to identify and rank key factors that affect the effectiveness of tourism policy and offer strategic recommendations for improving its development. The research adopts a mixed-method approach that encompasses qualitative insights, including expert interviews and extensive literature reviews, as well as quantitative data collected through a structured questionnaire based on ANP administered to experts, managers, and public decision makers in the tourism sector. Results indicate that, among others, human capital is the most important component of tourism development, followed by institutional/bureaucratic improvements, then accessibility. This emphasis on human capital is in line with endogenous growth theory, which underlines the role played by people in driving economic prosperity. On the other hand, institutional improvement promotes efficient policies for promoting tourism, while accessibility, although ranked lower, still remains crucial for enhancing visitors’ experiences. The recommendations for strategy consist of rigorous training for personnel in the tourism sector, the easing of license and permit procedures, and the development and enhancement of transportation and communication networks. The aim of these strategies is to promote a balanced and sustainable growth within the tourism industry. The study’s rigorous empiricism and theoretical framework offer strong support for the suggested strategies and make theoretical and application-level contributions to tourism management. In this research, by connecting the research results to the endogenous growth theory and supporting the results with a literature review, useful information and strategic solutions for international policymakers and stakeholders in Pamekasan Regency are provided.